Inequality within Philippine Provinces: Determinants and Validity of the Kuznets Curve - Libre, S.; Sarmiento, Jon (University of the Philippines at Davao, 2012)
Several studies evaluating the determinants of growth and poverty have been conducted, but there is limited literature on inequality determinants, in particular inequality of income distribution within Philippine provinces. Using a five-year panel data of 73 provinces, this study tests the validity of the Kuznets curve and evaluates the determinants of intraprovince inequality using Gini coefficient. The results show that the inverted U-shaped Kuznets curve is observed and that human and physical capitals are significant in decreasing both income and consumption inequality. There is lower inequality among agricultural households compared to non-agricultural households. However, agricultural households have lower average income. Policy interventions should prioritize human capital investment, address the poor income performance of agricultural households, and focus on more pro-poor growth policies.